Psychology On the Internet 1: Electronic Journals and Discussion Lists - Terre Blanche, Martin (PINS-Psychology in Society, 2026)
The internet has been described as an anthropologist’s paradise, as the symbol of the new world order, as a form of intellectual AIDS, as a super-panopticon and as the last undiscovered continent. Like it or not, if you are into the knowledge and power business in the post-apartheid, post-cold war, postmodern era, you will be caught up in the internet as surely as you would have ended up in a behaviourist’s clutches if these were the 60s. To hasten this in any case inevitable process, PINS may or may not be publishing an increasing number of papers on topics related to cyber-culture. In the first of this possible series we here bring you an entirely factual introduction to sources of academic information on psychology available to you by e-mail. Thus we have chosen both the most banal motive (information) and the most easily-mastered apparatus (e-mail) for our first demonstration. In future editions it is possible that we shall be exploring more deeply repressed motives and more complex state apparatuses.